Law Enforcement of Corruption Crimes in the Buru District Attorney's Office with Legal Certainty (Case Study: Decision No. 40/Pid.Sus-Tpk/2022/Pn.Amb) - Winanda, Gustian; Hafidz, Jawade (UNISSULA Semarang, 2025)
In enforcing corruption laws, the Prosecutor's Office has dual authority: conducting investigations, prosecuting, and enforcing criminal decisions. In practice, several obstacles remain, including difficulties in implementing decisions regarding payment of fines and restitution of state losses. This study aims to examine and analyze the enforcement of corruption laws at the Buru District Prosecutor's Office, the judge's considerations in Decision No. 40/Pid.Sus-Tk/2022/PN.Amb, and future corruption law enforcement in Indonesia. This research uses a sociological juridical approach, with descriptive analytical research specifications. The data used are primary and secondary data. Data collection methods include field studies and literature reviews, and data analysis methods are qualitative. The theories used in this research are the theory of justice, the theory of legal systems and the theory of legal certainty. Based on the research results it can be concluded that the law enforcement of corruption crimes at the Buru District Attorney's Office, particularly in decision Number 40/Pid.Sus-Tk/2022/PN.Amb, has complied with statutory regulations, both in investigations, indictments, prosecutions, and the implementation of judges' decisions. The judge's considerations in decision Number. 40/Pid.Sus-Tk/2022/PN.Amb are appropriate, namely by considering the fulfillment of the elements of the indictment, considering the level of guilt of the defendant, considering the category of state losses caused by the defendant's actions, considering the impact of the defendant's actions, and the benefits obtained by the defendant. In addition, the judge also considered the category of state losses based on the Sentencing Range Matrix of Supreme Court Regulation Number 1 of 2020. Through appropriate considerations, a fair decision was produced. Law enforcement of corruption crimes in Indonesia in the future by the prosecutor's office is to carry out investigations, prosecutions and implement judges' decisions in accordance with the authority regulated in the law. In the future, demands should always include additional penalties in the form of compensation for state losses, realizing criminal penalties for paying fines and compensation for state losses by making maximum efforts by collecting, confiscating assets and auctioning in accordance with statutory provisions and not implementing subsidiary penalties in the form of fines and compensation for convicts.